A pilot study on return of spontaneous Circulation among patients with Cardiopulmonary resuscitation performed in Emergency department, Hospital Universiti Sains Malaysia - Chew, Keng Sheng (2007)
Cardiopulmonary resuscitation (CPR) is an integral part of routine job prescription for emergcncy medicine doctors. Since the 1950s, the technique of CPR is ever improving. The introduction of the Utstein's style of reporting of outcomes or CPR has H.1l1her enhanced standardized research works in this vital area. The standardization of dctinitions and reporting template has also allowed more meaningful comparison of one study with another. Dcspitc that. there has not been many published works in this area in Malaysia. This pilot study serves to look into the effectiveness of CPR perli.)rmed in Emergcm;y Department (ED), Hospital Univcrsiti Sains Malaysiu (IIUSM). Two end points of this study arc I. whether return of spontaneous circulation (ROSe) achieved regardless of whether the Rose was sustained until admission to ward 2. whcther ROSe aehievcd and sustained until admission to ward. This is also known as survival to admission Methodology This study was conducted us a prospective. observational study. All patients with CPR done in ED. IIUSM were included in this study. The stuJy was undertaken for a period or one yl.:i.lr. from March 2005 to March 2006. <. 'ardiac arrl.:sl cases \\there CPR was nol pcrlilrllll.:J \-vere excluded lhllll the study. A total of 63 cardiac arrest patients were analyzed. Out of these 63 patients, 23 (36.5%) of the 63 patients were categorized as out-or-hospital Arrests (aHA) whereas the other 40 (63.5IVo) patients had an in-hospital Arrest (II-IA). In total. out of these 63 patients, 19 (30.2%) of them had ROSe regardless of whether the Rose was sustained until admission to ward. The other 44 (69.8%) did not achieve ROSe at all. Only 6 patients (9.5%) achieved ROSe until admission to ward (survival to admission) whereas the other 57 patients (90.5%) did not. In the aHA subgroup analysis. ROSe achieved regardless of whether it was sustained until admission to ward is only 17.4% (11=4) and Rose achieved until admission to ward is only 4.3% (n=l). In the lilA subgroup analysis, ROSe achieved regardless of whether it was sustained until admission to ward is slightly better at 37.5% (n~'I5) and ROSe achieved until admission to ward is slightly better at 12.5%) (n~5). The chance of a patient with IliA to achieve Rose regardless of whether the ROSe was sustained until admission to ward wu:; about two times (37S%) higher compared to a patient with OHA (17.4%) (p:-·O.094). Other factors found to be associated with higher chance or survival rate arc early commencement of CPR within 5 minutes. presence or emergency physicians during CPR. the presence or emergency medicine residents during CPR and shockable rhythm as the initial cardiac arrest rhythm. C